1994
DOI: 10.1044/jshr.3702.358
|View full text |Cite
|
Sign up to set email alerts
|

The Counting Abilities of Children With Specific Language Impairment

Abstract: This study examined the counting abilities of preschool children with specific language impairment compared to language-matched and mental-age-matched peers. In order to determine the nature of the difficulties SLI children exhibited in counting, the subjects participated in a series of oral counting tasks and a series of gestural tasks that used an invented counting system based on pointing to body parts. Despite demonstrating knowledge of many of the rules associated with counting, SLI preschool children dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 24 publications
2
47
1
2
Order By: Relevance
“…For instance, Fazio (1996Fazio ( , 1999 found that children with SLI evaluated at the age of 7 were still less efficient three years later. Furthermore, they made more errors and were slower than age-matched children at solving more complex calculation problems, and they tended to use a higher proportion of immature calculation strategies (e.g., finger counting) for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, Fazio (1996Fazio ( , 1999 found that children with SLI evaluated at the age of 7 were still less efficient three years later. Furthermore, they made more errors and were slower than age-matched children at solving more complex calculation problems, and they tended to use a higher proportion of immature calculation strategies (e.g., finger counting) for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 89%
“…for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used Number Skills in Children with SLI 8 to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 96%
See 1 more Smart Citation
“…Fluent and accurate counting is demanded to form associations in long-term memory between the problem presented and the answer and in helping to shift from counting-based strategies to fact retrieval, which is the fastest calculation strategy. Children with language impairment have also been found to have severe difficulty in counting (Donlan et al, 2007;Fazio, 1994Fazio, , 1999Koponen et al, 2006), which, in turn may explain their delay in developing calculation skill (Donlan et al, 2007). In addition, both counting and fact retrieval skills may share common processes (Donlan et al, 2007).…”
Section: Cognitive Predictors Of Single-digit and Procedural Calculatmentioning
confidence: 97%
“…Fazio (1994Fazio ( , 1996Fazio ( , 1999 suggests that working memory deficits are mainly responsible for the deficits in counting and knowledge of number facts that children with SLI show.…”
Section: Working Memorymentioning
confidence: 99%